Purification method of pegmatite high-purity quartz and extraction purity evaluation method
By combining geological observations and mature analytical techniques, multi-scale analysis and purification of high-purity quartz from pegmatites are carried out, solving the problems of complex purification methods and unscientific evaluation in existing technologies, and achieving efficient and low-cost purification and purity evaluation of high-purity quartz, meeting semiconductor and photovoltaic grade standards.
Patent Information
- Application Number
- CN202511009366.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-22
- Publication Date
- 2025-10-10
- Estimated Expiration
- 2045-07-22
AI Technical Summary
The existing technology lacks a high-precision purification method for high-purity quartz from pegmatites, and the existing quartz purification evaluation index factors are single and unscientific, resulting in high beneficiation costs and unstable purity.
By using naked eye observation, thin section observation under a microscope and whole rock analysis combined with laser confocal Raman spectroscopy, fluid inclusion temperature measurement and burst technology, combined with petrography, gas chromatography, liquid chromatography and mass spectrometry technology, high-temperature annealing, selective acid etching and physical separation methods, secondary fluid inclusions are removed to achieve the purification and purity evaluation of high-purity quartz.
It achieves rapid, simple and efficient purification of high-purity quartz from pegmatite, with a purity of 99.999%, meeting semiconductor and photovoltaic grade standards, providing important geological prospecting indicators, reducing beneficiation costs and improving purification accuracy.
Smart Images

Figure CN120757120A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of high-purity quartz purification, and particularly relates to a pegmatite high-purity quartz purification method and a purity evaluation method. BACKGROUND
[0002] With the rapid development of science and technology, high-purity quartz (SiO2 purity ≥ 99.998%) has become an irreplaceable key material in the fields of high technology such as semiconductors, photovoltaics, and new energy. For example, high-purity quartz is mainly used as a core material for the preparation of high-end electronic components such as semiconductor chips, optical fiber communication devices, and solar cells. The purity of high-purity quartz will directly affect the performance of these high-end electronic components.
[0003] The impurities of high-purity quartz mainly come from mineral lattice defects and fluid inclusions (gas-liquid, solid inclusions). The components such as Na + , K+, Li+, Ca 2+ , CO2 in the inclusions can significantly reduce the electrical properties (such as dielectric loss) and optical transmittance of quartz.
[0004] The existing quartz sand purification methods include five kinds: microwave-ultrasonic purification method, vacuum semi-melting-sand preparation purification method, multi-stage sorting-high temperature atmosphere purification method, flotation-magnetic separation combined purification method, and high temperature chlorination-alkali acid purification method. Microwave-ultrasonic purification method and vacuum semi-melting-sand preparation purification method can completely remove inclusions, have high efficiency of impurity removal, environmental optimization, energy saving and consumption reduction. However, they have the characteristics of complex equipment, high energy consumption, high equipment investment and maintenance cost, and difficult process control. The multi-stage sorting-high temperature atmosphere purification method has the problems of long complex process, huge equipment investment, and halogen treatment risk. The flotation-magnetic separation combined purification method has the characteristics of high efficiency of mineral separation, equipment innovation, and low energy consumption, but has the disadvantages of low upper limit of purity and wastewater treatment pressure. The high temperature chlorination-alkali acid combined purification method has the characteristics of extreme purity, complete removal of metal impurities, and high stability of mature process. However, it has the characteristics of high loss of special kiln refractory materials, strong corrosion of chlorine gas, and high difficulty of tail gas treatment, which has safety and environmental risks. It is particularly important to note that these methods are more focused on the purification and determination of quartz from the perspective of chemistry, mineral processing and smelting. However, in actual operation, there is a high threshold. Because the quality of quartz samples is unstable, that is, high-purity quartz is rare in high-quality mineral resources, impurities are unevenly distributed in different locations of the same vein, and not all quartz at the same location can meet the requirements of high-purity quartz. In particular, pegmatite quartz often develops in various structural zones of the entire pegmatite region (more than 50 km 2 Therefore, without basic geological sample judgment and microscopic screening, the use of complex mineral processing technology will greatly increase the cost of mineral processing and smelting.
[0005] In summary, it is imminent to select a low-cost, fast, simple and effective determination method, which provides an important index and prospecting direction for geological prospecting work. However, there is no high-precision purification method for pegmatite high-purity quartz in the prior art; moreover, the index factors considered in the prior art for evaluating and grading the purity of quartz extraction are single, and the evaluation is unscientific and unreasonable. SUMMARY
[0006] In view of the above analysis, the embodiments of the present application aim to provide a pegmatite high-purity quartz purification method and a purity extraction evaluation method to solve one or more of the above problems in the prior art.
[0007] The purpose of the present application is achieved as follows:
[0008] In one aspect, a pegmatite high-purity quartz purification method is provided, comprising the following steps:
[0009] S1, selecting a quartz sample C from the pegmatite high-purity quartz sample collected in the field by observing with the naked eye, observing the thin section under a microscope and whole rock analysis in sequence;
[0010] S2, performing laser confocal Raman spectrum measurement on the quartz sample C to obtain typical characteristic peak data and lattice Al data of fluid inclusions in the quartz sample C, and removing the quartz sample that does not meet the requirements based on the lattice Al data to obtain a quartz sample D;
[0011] S3, performing fluid inclusion temperature measurement on the screened quartz sample D to obtain the homogenization temperature of the fluid inclusions in the quartz sample D; and taking the quartz sample E with a homogenization temperature less than 600 DEG C as a preliminary purification product of pegmatite high-purity quartz.
[0012] Further, it further comprises:
[0013] S4, performing explosion on the preliminary purification product at an explosion temperature greater than 600 DEG C to obtain a quartz sample F, and the quartz sample F is the final purification product of pegmatite high-purity quartz.
[0014] Further, step S1 further comprises:
[0015] S11, preliminarily selecting a quartz sample A with a color of milky white, gray white or white and having a greasy luster by the naked eye, cutting the quartz sample A using a diamond wire saw or a precision cutting machine to prepare a double-side polished thin section with a thickness of <100 microns; and observing the thin section under a microscope to select a quartz sample B, the quartz sample B satisfying the following condition: the total area of pre-inclusion fluid inclusions in the range of the 50 times magnification field of view of the microscope is not higher than 1 square millimeter.
[0016] S12, the quartz sample B is subjected to whole rock testing, and quartz samples C are obtained by screening quartz samples with low impurities by XRD and LA-ICP-MS.
[0017] Further, in step S1, the selected quartz sample C satisfies the following conditions:
[0018] The SiO2 content of the quartz is Al < 50 ppm, Fe < 5 ppm.
[0019] Further, in S12, when the whole rock testing is performed, the quartz sample B is crushed into a powder of 60-80 mesh, and the powder is subjected to whole rock testing.
[0020] Further, in step S3, the fluid inclusions to be measured in the quartz sample D are determined by cathodoluminescence and general microscopy, and microthermometry is performed on the fluid inclusions in the quartz sample D using a cooling and heating stage to obtain the microthermometric data of the fluid inclusions in the quartz sample D.
[0021] On the other hand, a pegmatite high-purity quartz extraction purity evaluation method is also provided for evaluating the purity of the obtained quartz sample F; the evaluation method comprises the following steps:
[0022] S5, gas phase determination is performed on the fluid inclusions in the quartz sample F to obtain gas phase determination data;
[0023] S6, liquid phase determination is performed on the fluid inclusions in the quartz sample F to obtain liquid phase determination data;
[0024] S7, based on the experimentally determined gas phase determination data and liquid phase determination data, the impurity content R and the Ca 2+ , Li + , Na + + K + content of the fluid inclusions are obtained, and based on the impurity content R and the Ca 2+ , Li + , Na + + K + content of the fluid inclusions, the pegmatite high-purity quartz purification grade result is obtained.
[0025] Further, in step S7, the impurity content R of the fluid inclusions is calculated according to the following formula:
[0026]
[0027] In the above formula, m 流体 is the mass of the fluid inclusions per unit volume; and m 杂质 is the mass of the impurities in the fluid inclusions per unit volume.
[0028] Further, the pegmatite high-purity quartz purification grade result includes:
[0029] Class I: 8≤R<26ppm, and 2≤Ca 2+ <5ppm, 1≤Li + <5ppm, 5≤Na + +K + <16ppm;
[0030] Class II: 1≤R<8ppm, and 0.3≤Ca 2+ <2ppm, 0.2≤Li + <1ppm, 0.5≤Na + +K + <
[0031] 5ppm;
[0032] Class III: 0<R<1ppm, and 0<Ca 2+ <0.3ppm, 0<Li + <0.2ppm, 0<Na + +K +
[0033] <0.5ppm.
[0034] Further, in step S7, based on the volume, number and density of the fluid inclusions in the quartz sample F, the mass m of the fluid inclusions per unit volume is obtained 流体 ; the mass m of the impurities in the fluid inclusions per unit volume in the quartz sample F is obtained by a method of gas-liquid phase composition determination 杂质 .
[0035] Further, step S5 includes:
[0036] S51, the particle powder of the quartz sample F is subjected to super-clean cleaning, and the preliminary pretreatment is completed;
[0037] S52, the particle powder of the quartz sample F after super-clean cleaning is blown for 15 min at a temperature of 200℃, and the secondary pretreatment is completed;
[0038] S53, the particle powder of the quartz sample F after completing the secondary pretreatment is subjected to gas chromatography test, and the gas phase content data of the fluid inclusions are obtained.
[0039] Further, step S6 includes:
[0040] S61, one of a high-temperature annealing method, a chemical dissolution method or a physical separation method is used to pretreat the quartz sample F;
[0041] S62, ultrasonic extraction is carried out on the quartz sample F particle powder after pre-treatment, and an extraction liquid sample containing fluid inclusions is obtained; ion chromatography is carried out on the extraction liquid sample, and liquid phase determination data are obtained, including: Li + , Na + , K + , Ca 2+ , Mg 2+ .
[0042] Compared with the prior art, the pegmatite high-purity quartz purification method and the purity evaluation method provided by the application combine petrography, microthermometry, laser confocal Raman spectroscopy, gas chromatography, liquid chromatography and mass spectrometry (ICP-AES) tandem technology to perform multi-scale analysis on the gas-liquid phase components (H2O, CO2, Na + , K+, Li+, Ca 2+ , etc.) of the inclusions; and three methods of high-temperature annealing (near-melting-point constant-temperature treatment in an inert atmosphere), selective acid etching (HF vapor or aqua regia) and physical separation are adopted to effectively remove secondary fluid inclusions. On this basis, further purification of pegmatite high-purity quartz is realized by performing explosion at 600-800 DEG C on the preliminary purified product. The application comprehensively adopts basic geological observation and mature gas-liquid chromatography determination means, and the method is fast, simple, efficient, low in cost and environmentally friendly, which provides an important index for geological prospecting work.
[0043] The technical solutions described above in the application can also be combined with each other to realize more preferred combination solutions. Other features and advantages of the application will be described in the subsequent description, and some advantages will become apparent from the description or can be understood by implementing the application. The purposes and other advantages of the application can be realized and obtained from the contents specifically pointed out in the description and the drawings. BRIEF DESCRIPTION OF DRAWINGS
[0044] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings needed to be used in the embodiments or the prior art description will be briefly introduced. Obviously, the drawings in the following description are only some embodiments described in the embodiments of the present application, and other drawings can also be obtained by those skilled in the art according to these drawings.
[0045] Figure 1 Some pegmatite quartz samples selected in the embodiments of the present application;
[0046] Figure 2 Pegmatite quartz thin sections prepared in the embodiments of the present application and typical fluid inclusion characteristics under a microscope;
[0047] Figure 3The under-microscope image of the quartz sample D under cathodoluminescence and common microscope in the embodiment of the present application; wherein, a figure is the under-microscope image of the quartz sample D under cathodoluminescence; b figure and c figure are the fluid inclusion feature images of the quartz sample D under common microscope;
[0048] Figure 4 The operation flow schematic diagram of the pegmatite high-purity quartz purification method provided by the present application;
[0049] Figure 5 The operation flow schematic diagram of the pegmatite high-purity quartz purity extraction evaluation method provided by the present application. DETAILED DESCRIPTION
[0050] To make the purpose, technical scheme and advantages of the embodiments of the present application more clear, the technical scheme of the embodiments of the present application will be described clearly and completely below in combination with the drawings in the embodiments of the present application. Obviously, the described embodiments are some embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all the other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0051] To facilitate the understanding of the embodiments of the present application, the following will be further explained and described in specific embodiments in combination with the drawings. The embodiments do not constitute limitations on the embodiments of the present application. In the drawings, the size and relative size of the components can be exaggerated for clarity and / or descriptive purposes. When the exemplary embodiments can be implemented differently, the specific process sequence can be performed in an order different from that described. For example, two continuously described processes can be performed substantially simultaneously or in an order opposite to that described. In addition, the same reference signs represent the same components.
[0052] The terms used herein are for the purpose of describing specific embodiments and are not intended to be limiting. As used herein, the singular forms "a," "an," and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise. Furthermore, to the extent that the terms "including," "includes," "having," "has," "a," "an," "the," and / or variations thereof are used in either the detailed description and / or the claims, such terms are intended to be inclusive in a manner similar to the term "comprising" and / or "containing" as those terms are interpreted when employed as such terminology in the field of patent claims. It is also noted that, as used herein, the terms "substantially," "approximately," and other similar terms are used as synonyms for "about," and are employed to account for inherent variations in measuring, calculating, and / or providing a value and / or parameter.
[0053] Example 1
[0054] One specific embodiment of the present application, as shown in Figures 1 to 4 Figure 1, discloses a pegmatite high-purity quartz purification method, comprising the following steps S1-S3:
[0055] S1, select a quartz sample C from the pegmatite high-purity quartz sample collected in the field by observing with the naked eye, observing under a microscope, and whole rock analysis.
[0056] S11, from the collected pegmatite high-purity quartz sample, preliminarily select a quartz sample A that meets the requirements with the naked eye, prepare a quartz thin section, and observe the thin section under a microscope to select a quartz sample as a quartz sample B, which meets the following conditions: the total area of the pre-intrusion fluid inclusion in the range of the 50x magnification field of view under the microscope is not higher than 1 square millimeter.
[0057] The steps of preparing a thin section from a block sample: select a representative quartz ore sample with a milky white, grayish white or white color and a greasy luster from different zoning in the pegmatite by the naked eye, as shown in Figure 1 Cut the block quartz sample A selected by the naked eye using a diamond wire saw or a precision cutting machine to prepare a <100 μm thick double-sided polished thin section, as shown in Figure 2 to avoid the rupture of inclusions.
[0058] The specific steps of observing the thin section under a microscope: the magnification of the microscope is between 30-300; the light source of the microscope is a normal light source or a polarized light source; the image acquisition method includes: in the field of view, move the slide in the order of first from left to right, then from top to bottom, move 3-6 millimeters each time, ensure that there are no repeated particles in the photos, and specifically take 15-20 photos that can clearly observe the distribution of quartz fluid inclusions.
[0059] S12, further, whole rock test is performed on the quartz sample B, and based on the whole rock test results, further screening is performed to obtain the quartz sample C. That is, the quartz sample C is obtained by simultaneously screening the quartz sample with low impurities by XRD (XRD diffractometer) and LA-ICP-MS (laser ablation inductively coupled plasma mass spectrometer); the selected remaining quartz sample C meets the following conditions: the SiO2 content of the quartz is Al < 50 ppm, Fe < 5 ppm.
[0060] In step S12, when performing the whole rock test, the quartz sample B needs to be crushed into powder, and the powder is subjected to the whole rock test. Specifically, the selected quartz sample B is crushed, wet ground, filtered, concentrated and dried, and the ground powder sample is between 60 mesh and 80 mesh.
[0061] After removing the quartz samples that do not meet the requirements from the quartz sample B, the powder samples that meet the requirements, that is, the powder of the quartz sample C, are retained for use in the subsequent steps S2-S3.
[0062] S2. Perform laser confocal Raman spectroscopy on quartz sample C to obtain typical characteristic peak data and lattice Al data of the fluid inclusions in quartz sample C. Based on the lattice Al data, quartz samples that do not meet the requirements are eliminated to obtain quartz sample D.
[0063] Laser confocal Raman spectroscopy was used to analyze the single fluid inclusion in quartz sample C in situ, and the typical characteristic peak data and Al-OH defect peak (3580cm -1 ), directly remove the lattice Al 3 + contaminated quartz sample to obtain quartz sample D.
[0064] S3. Measure the fluid inclusion temperature of the screened quartz sample D to obtain the homogenization temperature of the fluid inclusions in the quartz sample D; select a quartz sample E with a homogenization temperature less than 600°C from the quartz sample D, and use the quartz sample E with a homogenization temperature less than 600°C as the preliminary purified product of pegmatite high-purity quartz.
[0065] Specifically, the fluid inclusions to be measured in the quartz sample D are first determined by cathode luminescence and ordinary microscopy, and the fluid inclusions in the quartz sample D are micro-measured using a hot and cold stage to obtain the temperature measurement data of the fluid inclusions in the quartz sample D; for example, according to Figure 3 Figure a is a microscopic image of quartz sample D under cathodoluminescence conditions. Determine the area where the fluid inclusion to be measured in quartz sample D is located, such as Figure 3 The inclusions in Figure b and Figure c; then, Figure 3 The fluid inclusions in quartz sample D (Figures b and c) were microthermographed. Based on the temperature data of the fluid inclusions in quartz sample D, the quartz samples with homogenization temperatures greater than 600°C were eliminated, resulting in quartz sample E.
[0066] When executing step S3, the type of fluid inclusions in the quartz sample E can be determined at the same time. According to the different types of fluid inclusions in the quartz sample E, the salinity and density data of the fluid inclusions in the quartz sample E can be obtained to prepare for the subsequent purity evaluation. When determining the type of fluid inclusions in the quartz sample E, the typical characteristic peak data include H2O (3400cm -1 )、CO2(1285 / 1388cm -1 ) peak data, based on H2O (3400 cm -1 )、CO2(1285 / 1388cm -1) peak, to determine the type of fluid inclusions in the quartz sample E, including two types: low salinity CO2 fluid inclusions and high salinity CO2-free fluid inclusions.
[0067] In step S3, the micro-temperature of the fluid inclusions in the quartz sample D is measured using a hot and cold stage, the freezing point (-100-0℃) data is determined by freezing method, and the salinity (0-23wt% NaCl eq) is calculated. All the test data of the quartz sample D obtained in this process contains the freezing point data required for calculating the salinity of the quartz sample E. Further, in combination with the type of fluid inclusions, the density p (g / cm 3 ) of different types of fluid inclusions in the quartz sample E is obtained.
[0068] According to the fluid inclusion temperature measurement data in step S3, the homogenization temperature of the high salinity CO2-free fluid inclusions in the quartz sample E with a homogenization temperature less than 600℃ is 500-600℃, and the homogenization temperature of the low salinity CO2-containing fluid inclusions is 200-300℃, which provides a reference basis for the subsequent step S4.
[0069] S4, the obtained preliminary purified product is burst to remove impurities in the inclusions in the quartz sample E, and the quartz sample F is obtained, which is the final purified product of the pegmatite high-purity quartz.
[0070] According to the fluid inclusion temperature measurement data in step S3, the homogenization temperature of the high salinity CO2-free fluid inclusions in the quartz sample E is 500-600℃, and the homogenization temperature of the low salinity CO2-containing fluid inclusions is 200-300℃. Based on this, the burst temperature T used in step S4 is greater than 600℃, and the burst time t is more than 10 min, for example, the burst temperature T is 600-800℃, and the burst time t is 15-30 min.
[0071] The embodiment also provides a pegmatite high-purity quartz extraction purity evaluation method for evaluating the purity of the quartz sample F obtained in step S4.
[0072] Referring to Figure 5 , the pegmatite high-purity quartz extraction purity evaluation method in the embodiment includes steps S5-S7:
[0073] S5, gas phase determination is performed on the fluid inclusions in the quartz sample F to obtain gas phase determination data.
[0074] S51, the particle powder of the quartz sample F is ultracleanly cleaned, and the preliminary pretreatment is completed.
[0075] Before the gas phase test, the particle powder of the quartz sample F needs to be ultracleanly cleaned, and is sequentially cleaned with acetone, ethanol, and ultrapure water for 10 minutes through ultrasonic cleaning to remove the surface contaminants of the particle powder of the quartz sample F.
[0076] S52, the particle powder of the quartz sample F after ultraclean cleaning is secondarily pretreated, and is blown at a temperature of 200 DEG C for 15 min.
[0077] Because the particle powder of the quartz sample F after ultraclean cleaning still adsorbs a small amount of water and air, which affects the determination of H2, O2, N2, CO, CO2, and H2O, therefore, according to the temperature measurement data result in step S3, the fluid inclusions and the surface impurities of the powder at a uniform temperature of 0-200 DEG C are further eliminated by blowing at a temperature of 200 DEG C for 15 min. When the air and H2O out of the peak are observed in the TCD channel of the chromatographic workstation, it is considered that the adsorbed water and air have been completely removed.
[0078] S53, the particle powder of the quartz sample F after the secondary pretreatment is tested, the gas phase content of the fluid inclusions is determined by gas chromatography, and the content data of H2, CO2, H2O, CH4, C2H2, C2H6, and C3H8 in the fluid inclusions are obtained.
[0079] S6, the fluid inclusions in the quartz sample F are determined by liquid phase, and the liquid phase determination data are obtained.
[0080] S61, the quartz sample F is pretreated by one of a high-temperature annealing method, a chemical dissolution method, or a physical separation method. Specifically as follows:
[0081] ① High-temperature annealing method.
[0082] The particle powder of the quartz sample F is heated to 50-200 DEG C below the mineral melting point in an inert atmosphere (such as Ar) for 24-48 hours, so that the internal pressure of the fluid inclusions exceeds the mineral strength, resulting in burst and releasing the contents, and the residual cavity is closed by mineral self-healing to complete the sample pretreatment.
[0083] ② Chemical dissolution method. Selective acid treatment can be performed by HF vapor etching or aqua regia treatment. Specifically as follows:
[0084] HF vapor etching step: the particle powder of the quartz sample F is placed in a sealed container, 40% HF vapor is introduced into the sealed container, the temperature is maintained at 60 DEG C, and the pretreatment of the sample is completed by maintaining for 2 hours to dissolve the inclusions around the matrix and retain the cavity.
[0085] The aqua regia treatment step is as follows: the particle powder of the quartz sample F is soaked in a mixed acid of HCl and HNO3 in a volume ratio of 3:1, the temperature of the mixed acid is 60 DEG C, after soaking in the mixed acid for 6 hours, the sample is placed on a heating plate at 200 DEG C for constant temperature for 3 hours, the metal inclusions are dissolved, and the sample is cleaned with ultrapure water until the ultrapure water has a conductivity value.
[0086] ③Physical separation method
[0087] The high-pressure hydraulic crushing method is used: the particle powder of the quartz sample F is mixed with ultrapure water, and the fluid inclusions are released by circulating crushing at a pressure of 200 MPa to complete the sample pretreatment.
[0088] S62, liquid phase fluid inclusion measurement is performed on the quartz sample F after pretreatment, and liquid phase measurement data is obtained.
[0089] S621, ultrasonic extraction is performed on the quartz sample F after explosion, and an extraction liquid sample containing fluid inclusions is obtained. Specifically, ultrasonic extraction is performed N times, 10 mL each time, and from the (N-1)th extraction liquid, almost no ions are detected, and the Nth extraction liquid has no ions detected, indicating that the fluid inclusions are completely in the extraction liquid, and the extraction liquid sample containing the fluid inclusions is obtained.
[0090] S622, ion chromatography test is performed on the extraction liquid sample, and liquid phase measurement data is obtained, including: Li + , Na + , K + , Mg 2+ , Ca 2+ , F - , Cl - , Br - , NO 2- , NO 3- , SO4 2- and other anions and cations.
[0091] S7, based on the experimental gas phase measurement data and liquid phase measurement data, the impurity content R and the Ca 2+ , Li + , Na + + K + content in the fluid inclusions are obtained, and according to the impurity content R and the Ca 2+ , Li + , Na + + K + content in the fluid inclusions, the pegmatite high-purity quartz purification grade result is obtained, and specifically the pegmatite high-purity quartz purification grade is divided into I, II and III.
[0092] S71, define the mass percentage of impurities contained in the unit area fluid inclusion as the impurity content R in the fluid inclusion, and calculate the impurity content R in the fluid inclusion according to the following formula:
[0093]
[0094] In the above formula, m 流体 is the mass of the fluid inclusion per unit volume; m 杂质 is the mass of the impurities in the fluid inclusion per unit volume;
[0095] S711, based on the volume, number and density of the fluid inclusions in the quartz sample F, the mass m 流体 of the fluid inclusion per unit volume is obtained.
[0096] The volume and number of fluid inclusions in the quartz sample F can be calculated according to the following method:
[0097] Method one: microscopic observation, observe the shape, size and distribution of fluid inclusions by petrographic microscope, record the volume of single inclusion and the number per unit area.
[0098] Method two: three-dimensional reconstruction, estimate the three-dimensional volume of the inclusion by Raman imaging or gravity method, and calculate the total inclusion volume combined with the distribution density.
[0099] The mass m 流体 of the fluid inclusion per unit volume is calculated according to the following steps:
[0100] The volume of the fluid inclusion is V = h x S, h is the cross-sectional height, h value can be taken as 1, then the mass m 流体 of the fluid inclusion per unit volume is:
[0101] m 流体 = pV = p hS = pS.
[0102] In the formula, m 流体 is the mass of the fluid inclusion per unit volume; p is the density of the fluid inclusion; S is the total area of the linear assembly of multiple fluid inclusions in a single field of view.
[0103] Wherein, the p of single fluid inclusion can be obtained according to the microthermometry of fluid inclusion, see step S4 for details; the total area of the linear assembly of multiple fluid inclusions in a single field of view is calculated as follows:
[0104] Assuming that the fluid inclusion is approximately circular, the linear assembly of fluid inclusions can be understood as a linear inclusion combination body composed of a plurality of circular fluid inclusions arranged densely.
[0105] Suppose there are m linear inclusion combination bodies, numbered 1, 2, i, …, m respectively.
[0106] Take the linear inclusion combination analysis numbered i, the linear direction is the x axis, and the row number of the linear inclusion combination is n (i) (x), the diameter of a single fluid inclusion is f (i) (x), the length of a single linear inclusion combination is l (i) .
[0107] Therefore:
[0108] The area of a single linear inclusion combination is:
[0109] The total area S of a plurality of linear fluid inclusion assemblies is:
[0110]
[0111] S712, by the method of gas-liquid phase component determination, obtain the mass m of impurities in a unit volume of fluid inclusions in the quartz sample F 杂质 . Wherein, the mass m of the unit volume of fluid inclusions 流体 The weight of water, impurities in fluid inclusions and gas phase components.
[0112] S713, substituting m 杂质 And m_ 流体 Into the formula , the calculation formula of the impurity content R in the fluid inclusion is:
[0113]
[0114] S72, according to the impurity content R in the fluid inclusion and the Ca 2+ , Li + , Na + +K + content in the liquid phase determination data, the pegmatite high-purity quartz purification grade is divided into I, II, III, which respectively correspond to the high-purity quartz, ultra-high-purity quartz and super-purity quartz proposed by Harben. Specifically as follows:
[0115] I: 8≤R<26ppm, and 2≤Ca 2+ <5ppm, 1≤Li + <5ppm, 5≤Na + +K + <16ppm.
[0116] II: 1≤R<8ppm, and 0.3≤Ca 2+ <2ppm, 0.2≤Li + <1ppm, 0.5≤Na + +K+ <
[0117] 5ppm.
[0118] III: 0 < R < 1 ppm, and 0 < Ca 2+ <0.3 ppm, 0 < Li + <0.2 ppm, 0 < Na + + K +
[0119] <0.5 ppm.
[0120] After purification by experiment, the SiO2 content of the pegmatite type high-purity quartz product reaches 99.9983%, and the product purity grade reaches 4N8.
[0121] According to the experimental results in Table 1, the purification grade of the quartz sample No. 3 is III grade, the purification grade of the quartz sample No. 2-10 is II grade, and the purification grade of the quartz sample No. 11 is III grade.
[0122] Table 1 Fluid inclusion liquid phase component and gas phase component
[0123]
[0124] Compared with the prior art, the pegmatite high-purity quartz purification method and the pegmatite high-purity quartz extraction purity evaluation method provided by the embodiment have the following beneficial effects:
[0125] (1) The application combines petrography, microthermometry, laser confocal Raman spectroscopy, gas chromatography, liquid chromatography and mass spectrometry (ICP-AES) tandem technology to analyze the gas-liquid phase components (H2O, CO2, Na + , K+, Li+, Ca 2+ , etc.) of the inclusions in multiple scales; and three methods of high-temperature annealing (constant temperature treatment near the melting point in an inert atmosphere), selective acid etching (HF vapor or aqua regia) and physical separation are used to effectively remove secondary fluid inclusions. On this basis, further purification of pegmatite high-purity quartz is realized by exploding the preliminary purified product at 600-800℃. The application involves basic geological observation and mature gas-liquid chromatography determination means, and the method is fast, simple, efficient, low in cost and environmentally friendly, which provides an important index for geological prospecting work.
[0126] (2) The fluid inclusions are accurately positioned through geological hand specimen observation and in-situ observation under a microscope, and the type of the fluid inclusions and the impurity distribution rule are identified; further, by controlling the specific explosion temperature of the fluid inclusions, the inclusions impurities can be removed in a directional manner, and the impurities can be reduced to ppb level by physical-chemical synergistic method, which helps to improve the purification accuracy of high-purity quartz.
[0127] (3) The quartz extracted by the application has a purity of ≥99.999%, and there is basically no residual inclusion. The application can minimize the influence of fluid inclusions in high-purity quartz, meeting the standards of semiconductor-grade (5N) and photovoltaic-grade (4N8) quartz sand.
[0128] The above detailed description further illustrates the purpose, technical solutions and beneficial effects of the application. It should be understood that the above description is only a specific embodiment of the application and is not used to limit the protection scope of the application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the application shall be included in the protection scope of the application.
Claims
1. A method for purifying high-purity quartz from pegmatite, characterized in that: The steps include: S1. Quartz sample C was selected from high-purity quartz samples of pegmatite collected in the field by visual observation, microscopic thin section observation, and whole-rock analysis. S2. Performing laser confocal Raman spectroscopy on quartz sample C to obtain typical characteristic peak data and lattice Al data of fluid inclusions in quartz sample C. Based on the lattice Al data, quartz samples that do not meet the requirements are eliminated to obtain quartz sample D. S3. Measure the fluid inclusion temperature of the screened quartz sample D to obtain the homogenization temperature of the fluid inclusions in the quartz sample D; and use the quartz sample E with a homogenization temperature less than 600° C. as the preliminary purified product of pegmatite high-purity quartz.
2. The method for purifying high-purity quartz from pegmatite according to claim 1, wherein: Also includes: S4. Exploding the preliminarily purified product at a blasting temperature greater than 600° C. to obtain a quartz sample F, which is the final purified product of pegmatite high-purity quartz.
3. The method for purifying high-purity quartz from pegmatite according to claim 1 or 2, wherein: Step S1 further includes: S11. Preliminarily select quartz sample A with a milky white, off-white, or white color and an oily luster by visual inspection. Cut quartz sample A using a diamond wire saw or a precision cutting machine to prepare double-sided polished thin sections with a thickness of less than 100 μm. Observe the thin sections under a microscope to select quartz sample B. Quartz sample B meets the following conditions: within the field of view of a microscope at 50x magnification, the total area of the fluid inclusions within the sample is no greater than 1 square millimeter. S12. Perform whole-rock testing on quartz sample B, and pre-screen quartz low-impurity samples using XRD and LA-ICP-MS to obtain quartz sample C.
4. The method for purifying high-purity quartz from pegmatite according to claim 3, wherein: In step S1, the selected quartz sample C meets the following conditions: The SiO2 content of quartz is Al<50ppm, Fe<5ppm.
5. The method for purifying high-purity quartz from pegmatite according to claim 3, wherein: In S12, when performing the whole rock test, the quartz sample B is crushed into 60-80 mesh powder, and the powder is subjected to the whole rock test.
6. The method for purifying high-purity quartz from pegmatite according to claim 1, wherein: In step S3, the fluid inclusions to be measured in the quartz sample D are first determined by cathode luminescence and ordinary microscopy, and the fluid inclusions in the quartz sample D are microscopically measured using a hot and cold stage to obtain temperature measurement data of the fluid inclusions in the quartz sample D.
7. A method for evaluating the purity of high-purity quartz extracted from pegmatite, characterized in that: Used to evaluate the purity of the quartz sample F obtained in claim 2; The evaluation method comprises the following steps: S5. Performing gas phase measurement on the fluid inclusions in the quartz sample F to obtain gas phase measurement data; S6. performing liquid phase measurement on the fluid inclusions in the quartz sample F to obtain liquid phase measurement data; S7. Based on the experimental gas phase measurement data and liquid phase measurement data, the impurity content R and Ca in the fluid inclusion are obtained. 2+ 、Li + 、Na + +K + Content, according to the impurity content R and Ca in the fluid inclusion 2+ 、Li + 、Na + +K + content, and obtain the purification grade results of pegmatite high-purity quartz.
8. The method for evaluating the purity of pegmatite high-purity quartz extraction according to claim 7, wherein: In step S7, the impurity content R in the fluid inclusion is calculated according to the following formula: In the above formula, m 流体 is the mass of fluid inclusion per unit volume; m 杂质 is the mass of impurities in the fluid inclusion per unit volume.
9. The method for extracting and evaluating the purity of pegmatite high-purity quartz according to claim 8, wherein: The pegmatite high purity quartz purification grade results include: Level I: 8≤R<26ppm, and 2≤Ca 2+ <5ppm、1≤Li + <5ppm、5≤Na + +K + <16ppm; Level II: 1≤R<8ppm, and 0.3≤Ca 2+ <2ppm、0.2≤Li + <1ppm, 0.5≤Na + +K + < 5ppm; Level III: 0<R<1ppm, and 0<Ca 2+ <0.3ppm、0<Li + <0.2ppm、0<Na + +K + <0.5ppm.
10. The method for extracting and evaluating the purity of pegmatite high-purity quartz according to claim 8, wherein: In step S7, based on the volume, number and density of the fluid inclusions in the quartz sample F, the mass m of the fluid inclusions per unit volume is obtained. 流体 By measuring the gas-liquid phase composition, the mass m of impurities in the fluid inclusions per unit volume of the quartz sample F is obtained. 杂质 ; Preferably, step S6 includes: S61, pre-treating the quartz sample F by using one of a high-temperature annealing method, a chemical dissolution method, or a physical separation method; S62. Perform ultrasonic extraction on the pre-treated quartz sample F particle powder to obtain an extract sample containing fluid inclusions; perform ion chromatographic testing on the extract sample to obtain liquid phase measurement data, including: Li + 、Na + , K + , Ca 2+ Mg 2+ .
Citation Information
Patent Citations
Determination method of quartz alpha-beta phase change P-T relationship
CN113655047A
Method for removing pegmatite fluid-rich inclusion quartz sand
CN118634987A
Quartz raw ore process mineralogy analysis method and method for judging whether quartz raw ore can serve as high-purity quartz raw ore or not
CN119534520A
A METHOD FOR OBTAINING HIGH-PURITY CONCENTRATE FROM NATURAL QUARTZ
RU2009132430A